Sensitivity studies for volume averaged models of plasma etch reactors - Kleditzsch, Stefan; Riedel, Uwe (Surface and coatings technology, 2001)
A well-stirred reactor model is employed to model the etching of silicon in low pressure chlorine/argon plasmas. The model gives the spatially averaged species composition and etch rate in a plasma etch reactor by solving conservation equations for species, mass and electron energy distribution function (EEDF). Systematic sensitivity analyses, made possible by a new iterative approach, allows the identification of key parameters for improved fault detection and model based process control of plasma reactors.